2010
DOI: 10.1189/jlb.0610333
|View full text |Cite
|
Sign up to set email alerts
|

A caveat for T cell transfer studies: generation of cytotoxic anti-Thy1.2 antibodies in Thy1.1 congenic mice given Thy1.2+ tumors or T cells

Abstract: Thy1.1 congenic B6.PL mice were used to simultaneously monitor Thy1.2+ E.G7-OVA tumors transplanted in the a.c. of the eye and i.v.-transferred tumor-specific Thy1.2+ CTLs to determine mechanisms that inhibit the tumoricidal activity of CTL responses in mice with established ocular tumors. Transferred CTLs were systemically deleted in mice with established ocular tumors. However, this deletion was not a unique mechanism of immune evasion by ocular tumors. Rather, development of Thy1.2+ tumors in the eye or ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In published work, donor T cells are generally well tolerated by recipient mice. Nevertheless, there are a few documented cases of immune responses elicited by transferred cells that differed at the CD45 or Thy1 loci [16][17][18][19][20]. While such donor/recipient pairs are often considered to be "congenic", it is clear that multiple genes are included in the congenic interval.…”
Section: Introductionmentioning
confidence: 99%
“…In published work, donor T cells are generally well tolerated by recipient mice. Nevertheless, there are a few documented cases of immune responses elicited by transferred cells that differed at the CD45 or Thy1 loci [16][17][18][19][20]. While such donor/recipient pairs are often considered to be "congenic", it is clear that multiple genes are included in the congenic interval.…”
Section: Introductionmentioning
confidence: 99%
“…[ transplanted into donor mice expressing the other allotype (CD90.2) or wildtype background, respectively. These experiments showed that both factors are capable of triggering an immune response [35][36][37]. It should be kept in mind that mouse strains are differentially capable of mounting immune responses to certain tracking molecules, with BALB/c mice being more immunocompetent against eGFP than C57BL/6 [38].…”
Section: Gut Microbiotamentioning
confidence: 93%
“…The procedures used in this experiment have been published previously [ 33 ]. Briefly, splenocytes were harvested from CD45.2 + OT-1 mice, and CD8 + T cells were purified using the MACS CD8 + T Cell Isolation Kit (Miltenyi Biotec, Bergisch Gladbach, Germany), according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%